Healthy lifestyle interventions in general practice - E.W. Derman; S. Whitesman; M. Dreyer; D.N. Patel; C.J. Nossel; M.P. Schwellnus (South African Family Practice)
This article forms the second part of the series on the role of lifestyle modification in general practice with specific reference to chronic cardiovascular disease. Whilst the major risk factors which constitute an unhealthy lifestyle were discussed in part 1of this series, the focus of part 2 will give specific practical guidelines which the general practitioner may incorporate into their practice when counselling patients with chronic cardiovascular disease.